53.2k views
3 votes
Solve 3(x-4) = 12x. circle your final solution

User Henderunal
by
4.6k points

2 Answers

2 votes

Answer: x = -4/3

Explanation:

3(x−4)=12x

Step 1: Simplify both sides of the equation.

3(x−4)=12x

(3)(x)+(3)(−4)=12x (Distribute)

3x+−12=12x

3x−12=12x

Step 2: Subtract 12x from both sides.

3x−12−12x=12x−12x

−9x−12=0

Step 3: Add 12 to both sides.

−9x−12+12=0+12

−9x=12

Step 4: Divide both sides by -9.

-9x/-9 = 12/-9

x = -4/3

User Caspar Kleijne
by
5.3k points
5 votes

Answer:

9x-12

Explanation:

3*x = 3x

3*-4= -12

3x - 12 = 12x

12x-3x = 9x

9x-12

User Dolbysurnd
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.